Arab Film and Video Manifestos Forty-Five Years of the Moving Image Amid Revolution - Dickinson, Kay (Palgrave Studies in Arab Cinema, 2018)
Arab Film and Video Manifestos presents, in their entirety, five key documents that have fundamentally shaken up and helped change the face of image culture in the Middle East and beyond. The book collects together, for the first time, these influential, collectively written calls and directives that span a fifty-year period and hail from a range of different countries. Each urges a radical rethinking of film and video's role in culture, its relation to politics, and its potential to instigate profound change. Kay Dickinson carefully positions the manifestos within their broader socio-historical contexts and provides supplementary reading and viewing suggestions for readers who cannot access Arabic-language sources.